2019
DOI: 10.1093/qjmed/hcz166
|View full text |Cite
|
Sign up to set email alerts
|

Proton pump inhibitor use and progression to major adverse renal events: a competing risk analysis

Abstract: Background Proton pump inhibitors (PPIs) are associated with acute tubulointerstitial nephritis and there are reports associating their use with the development of chronic kidney disease (CKD). Aim To determine if PPI use is associated with major adverse renal events (MARE) in patients with CKD. Design Observational cohort study comprising patients with CKD a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 31 publications
1
20
1
Order By: Relevance
“…Proponents of population based epidemiology argue that the 3 year randomized controlled trial was still too small and too short to detect rare long term adverse events associated with PPI use. Instead they point to the many population based studies and meta-analyses of PPI risks summarized in table 3 8081828384858687888990919293949596979899100101. However, the mechanistic hypotheses that link these adverse outcomes to PPI use are without support from experimental studies.…”
Section: Managementmentioning
confidence: 99%
“…Proponents of population based epidemiology argue that the 3 year randomized controlled trial was still too small and too short to detect rare long term adverse events associated with PPI use. Instead they point to the many population based studies and meta-analyses of PPI risks summarized in table 3 8081828384858687888990919293949596979899100101. However, the mechanistic hypotheses that link these adverse outcomes to PPI use are without support from experimental studies.…”
Section: Managementmentioning
confidence: 99%
“…Despite the growing body of evidence on PPI use and increased risk for developing CKD, there is limited data on patients with already established CKD. To the best of our knowledge, only one such study has been published [16]. It concluded that PPI use was associated with increased major renal adverse events, defined as doubling of serum creatinine or progression to end-stage renal disease.…”
Section: Introductionmentioning
confidence: 99%
“…15 The study done by Grant and colleagues concluded that PPI use is associated with increased risk of major adverse renal events. 16 This study is the only other study, to date, to look at PPI safety speci cally in the CKD population. However, there are several important distinctions between Grant's study and our own, which could account for the differences seen in our results.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only one such study has been published. 16 It concluded that PPI use was associated with increased major renal adverse events, de ned as doubling of serum creatinine or progression to end-stage renal disease.…”
Section: Introductionmentioning
confidence: 99%